2015
DOI: 10.1161/jaha.115.001888
|View full text |Cite
|
Sign up to set email alerts
|

Implications of the US Cholesterol Guidelines on Eligibility for Statin Therapy in the Community: Comparison of Observed and Predicted Risks in the Framingham Heart Study Offspring Cohort

Abstract: BackgroundConcerns have been raised that the 2013 atherosclerotic cardiovascular disease (ASCVD) risk estimator overpredicts risk in contemporary cohorts. Whether suboptimal calibration will lead to overtreatment with statins is unknown. We investigated the numbers of people eligible for statin treatment in the Framingham Heart Study Offspring Cohort, based on the 2013 cholesterol guidelines, and estimated the proportion that may be overtreated as a result of potential miscalibration of the ASCVD estimator.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(14 citation statements)
references
References 21 publications
2
12
0
Order By: Relevance
“…Some of these differences might be explained by our population being more similar to the cohorts used in constructing the FRS and PCE than MESA. Our finding that the recently proposed PCE had worse calibration than the FRS is consistent with some recent literature that has shown mixed results in validating the PCE in diverse populations . The PCE may suffer somewhat from being overfitted to the longitudinal cohort study data from which it was derived, which negatively affects its calibration in new settings.…”
Section: Discussionsupporting
confidence: 82%
“…Some of these differences might be explained by our population being more similar to the cohorts used in constructing the FRS and PCE than MESA. Our finding that the recently proposed PCE had worse calibration than the FRS is consistent with some recent literature that has shown mixed results in validating the PCE in diverse populations . The PCE may suffer somewhat from being overfitted to the longitudinal cohort study data from which it was derived, which negatively affects its calibration in new settings.…”
Section: Discussionsupporting
confidence: 82%
“…Predicted ASCVD risk using the equation was reported to be systematically higher than observed risk in some highly selected cohorts (3,4), but not in others (5). Importantly, however, these studies included persons screened for participation or enrolled in clinical trials, or in much earlier time periods, with limited generalizability to contemporary and diverse populations that are more representative of eligible patients treated in typical clinical practice (6,7).…”
Section: Introductionmentioning
confidence: 78%
“…Therefore, secular trends in statin use, revascularization procedures, or treatment of other risk factors such as hypertension and diabetes, may account for the lower rates of CVD observed in more contemporary cohorts. 2729 Underascertainment of clinically relevant events in the validation cohorts may also explain the apparent overestimation. In fact, when investigators used Medicare claims data to improve outcome ascertainment for the REGARDS study, they demonstrated improved performance of the pooled cohort equations.…”
Section: Guidelines For the Treatment Of Blood Cholesterolmentioning
confidence: 99%